HIV Risks among Female Sex Workers in Croatia and Montenegro - Štulhofer, Aleksandar; Laušević, Dragan; Božičević, Ivana; Mugoša, Boban; Terzić, Nataša; Drglin, Tihana; Baćak, Valerio (2010)
The study analyzed the prevalence and determinants of HIV-risks among female sex workers (FSWs) in Croatia and Montenegro. Face-to-face interviews were carried out in Zagreb, Split, and Podgorica during the 2006-2008 period. Croatian participants (n=154) reported fewer clients, more consistent condom use, higher rates of HIV testing, and greater HIV knowledge. The participants interviewed in Montenegro (n=119) were more likely to have injected drugs and to have experienced sexual abuse in the previous year. Although Montenegrin FSWs were more exposed to HIV-risks than Croatian FSWs, they reported lower HIV-risk self-assessment. Consistent condom use was significantly associated with education and HIV-risk self-assessment in the Croatian and the experience of physical/sexual abuse in the Montenegrin sample. In spite of a number of methodological limitations, the empirical insights provided by this study may assist in improving the existing HIV prevention initiatives.
Projekt MZOS
ENG